2008
DOI: 10.1007/s00264-008-0550-y
|View full text |Cite
|
Sign up to set email alerts
|

Tibial lengthening using a reamed type intramedullary nail and an Ilizarov external fixator

Abstract: The aim of this study was to evaluate the efficacy of tibial lengthening using a reamed type intramedullary nail and an Ilizarov external fixator for the treatment of leg length discrepancy or short stature. This retrospective study was performed on 18 tibiae (13 patients) in which attempts were made to reduce complications. We used an Ilizarov external fixator and a nail (10 mm diameter in 17 tibiae and 11 mm in one tibia) in combination. Average limb lengthening was 4.19 cm (range, 2.5-5.5). The mean duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 23 publications
0
21
0
2
Order By: Relevance
“…The HI corresponds to the ratio of the number of days an EF is in place compared to the amount of lengthening measured in centimeters [5]. This is reduced by very regular lengthening of 1 mm per day distributed over 60 days using automatic distraction osteosynthesis [6][7][8], by multifocal and/or multisegmental lengthening [9], or by adding intramedullary implants such as nails [10][11][12][13][14][15][16][17] or elastic stable intramedullary nailing (ESIN) [18][19][20][21]. This association of intramedullary implants with EFs has made it possible to lower the rate of deformities and fractures after removal of the EF.…”
Section: Introductionmentioning
confidence: 99%
“…The HI corresponds to the ratio of the number of days an EF is in place compared to the amount of lengthening measured in centimeters [5]. This is reduced by very regular lengthening of 1 mm per day distributed over 60 days using automatic distraction osteosynthesis [6][7][8], by multifocal and/or multisegmental lengthening [9], or by adding intramedullary implants such as nails [10][11][12][13][14][15][16][17] or elastic stable intramedullary nailing (ESIN) [18][19][20][21]. This association of intramedullary implants with EFs has made it possible to lower the rate of deformities and fractures after removal of the EF.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, if the external fixator is removed too early, it may result in axial deviation or refracture. Since Paley et al first described it in 1997 [4], the surgical technique of lengthening over an intramedullary (IM) nail has gained wide acceptance because it reduces the duration required for external fixation and offers considerable improvements in patients' comfort [5]. However, Watanabe et al have reported that they encountered such a high rate of serious complications in patients treated with lengthening over an IM nail, including cases of deep infection and breakage of nails or locking screws, that they abandoned this technique and returned to the classic Ilizarov method [6].…”
Section: Introductionmentioning
confidence: 99%
“…The combined techniques resulted in the reduction of the usual IEF duration and good union rates [35]. There were many clinical studies of using the external fixator over the nail or FIN for orthopaedic conditions and injuries [4, 5, 11, 12]. …”
Section: Discussionmentioning
confidence: 99%